ELDERLY POST STROKE PATIENTS - I Gede Nova Tesa Prajawan; I Nyoman Astika; Ni Putu Ayu Krisna Yuniastuti; Baiq Riana Lahastri (Jurnal Delima Harapan, 2023)
Old age (elderly) is a natural process that cannot be avoided by every individual. As the economy and people's lives develop, the level of health care and increasing life expectancy make the elderly population the most important social problem in the world. The disease that often occurs in the elderly is stroke. Clinically, the physical disorders experienced by stroke patients include paralysis, namely weakness in one part of the body, difficulty moving and walking, decreased stamina, pain, numbness, very sensitive taste and loss of awareness of the position of the hand movements. This study aims to determine the general description of post-stroke elderly patients related to mobilization. This type of research is a qualitative design with a case study approach. The measuring tools used in this study are interviews, observation and documentation. The respondent's daily meals are normal, nutritional status is at risk of malnutrition, Activity Daily of Living (ADL) is totally dependent, the ADL instrument is done by other people, depression and tends to be sensitive, at risk of pressure ulcers, sleep disturbances occur during the day days, psychiatric disorders, sricardial disorders and there are symptoms of insomnia. Based on the results that have been carried out during a comprehensive assessment of the elderly after stroke, it was found that there was a morbidity/mobilization disorder. It is hoped that health workers will provide follow-up interventions in order to assist families in and improve knowledge, attitudes and skills as well as caring for elderly patients after stroke.